Language cues in the formation of hierarchical representations of space. Issue 3 (3rd July 2019) - Schick, Wiebke; Halfmann, Marc; Hardiess, Gregor; Hamm, Friedrich; Mallot, Hanspeter A.
ABSTRACT: We study the role of place and region names in the formation of spatial hierarchies. Representations were probed behaviorally, i.e., by choices between two equidistant routes differing only in the number of regions they touched. Routes crossing fewer region boundaries are preferred over routes crossing more region boundaries. Visual landmark objects from a common semantic category placed in spatial vicinity induce region representations. Here we show that region dependent route preference is reduced if the landmark objects are replaced by signs displaying object names. The effects of explicit region names and linguistic properties of different naming schemes are discussed.